КОНЦЕПТУАЛЬНІ АСПЕКТИ ФОРМУВАННЯ ПРАВОВОЇ МОДЕЛІ СТАЛОГО РОЗВИТКУ УКРАЇНИ - Ustymenko, V.A.; Dzhabrailov, R.A.; Malolitneva, V.K.; Hudima, T.S. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2021)
It has been found that the methodological principles of building a legal model of sustainable development of Ukraine remain imperfect. In this regard, it is argued that the basis of the legal model, first of all, shall be assigned general and sectoral legal principles that will create the theoretical base of normative activity. In particular, it has to be that the Rule of Law principle has a particularly specific content and acquires signs of a particular legal instrument in the process of law-making and law enforcement. Accordingly, the use of the Rule of Law principle in the process of assessing the efficiency of legal norms is proposed, which will talk about promoting the legal act of the ideology of justice. It is necessary to unacceptable laying into the legal model of sustainable development of the false concept of legal regulation of economic relations, which provides for the exclusion from the legal system of the state of certain branches of legislation, in particular economic legislation. It is substantiated that the Economic Code of Ukraine is the basis for achieving the goals of sustainable development on the economic component and synergistic associated with other acts of Ukrainian legislation in the environmental and social spheres. In this regard, it is argued that the effectiveness of the legal model of sustainable development will be significantly higher, subject to preservation in the legal system of the Economic Code of Ukraine, which will additionally testify to compliance with the Rule of Law principle. It is emphasized that in the light of the adaptation of Ukrainian legislation, including economic, to the EU Law and the signing of the Association Agreement between Ukraine and the EU, the influence of international legal norms on the state and directions of development of individual institutions of Economic law, which contributes to the universalization of the legal model of the steady the state's development. REFERENCES